Pembuatan Teknologi Tepat Guna Spinner sebagai Alat Alternatif Peniris Minyak - Cantikasari, Sugma; Wahyu Ali Mashuri, Dandy; Ella Mustika , Elit; Tarigan, Elkana Yolanda; Bintang Rafi, Ken; Firdaus Setiawan, Risqi (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
Mushrooms are one of the many plant commodities consumed and cultivated by Indonesian people. Crispy mushroom is a processed product of UMKM KWT Sri Rejeki which is in great demand by consumers. This production activity continues to experience development by facing various kinds of obstacles that occur, one of which is in the packaging process where the packaged mushrooms release residual frying oil so that they require Appropriate Technology (TTG) in the form of a spinner or oil drainer. So that KKN-T Group 29 students from Universitas Pembangunan Nasional "Veteran" Jawa Timur, designed a tool to help UMKM KWT Sri Rejeki drain the oil in the crispy mushrooms so that they are of higher quality. This tool assembly activity was carried out by KKN-T Group 29 students with several tools and materials that were easily available and affordable.